2011
DOI: 10.1098/rsbl.2011.0454
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence that women's mate preferences are directly influenced by cues of pathogen prevalence and resource scarcity

Abstract: When choosing a mate, women are thought to face a trade-off between genetic and parental quality. Recent research suggests that this trade-off is influenced by environmental factors such as pathogen prevalence and resource scarcity, which affect the relative value of genetic and parental quality to offspring fitness. To further investigate these findings, the current study primed 60 women with pathogen prevalence, resource scarcity or an irrelevant threat, before administering a forced trade-off task that asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 20 publications
2
87
1
1
Order By: Relevance
“…Previous studies suggest that priming women with cues to financial/environmental harshness decreases their masculinity preferences (Little et al , 2013b; see also Lee and Zietsch 2011), which has been interpreted as evidence that harsh environments may favour the choice of lower-quality but higher-investing (long-term) partners. Instead of priming participants with hypothetical scenarios, we tested whether perceived financial resource scarcity affects masculinity preferences.…”
Section: P2: Resource Availabilitymentioning
confidence: 99%
“…Previous studies suggest that priming women with cues to financial/environmental harshness decreases their masculinity preferences (Little et al , 2013b; see also Lee and Zietsch 2011), which has been interpreted as evidence that harsh environments may favour the choice of lower-quality but higher-investing (long-term) partners. Instead of priming participants with hypothetical scenarios, we tested whether perceived financial resource scarcity affects masculinity preferences.…”
Section: P2: Resource Availabilitymentioning
confidence: 99%
“…Again, it was found that women with high pathogen disgust were more likely to choose the masculine face. This effect appears to persist across several levels of analysis, not only across individuals with differences in pathogen disgust predicting masculinity preference (DeBruine, Jones, Tybur et al, 2010;Jones, Fincher, Little, & DeBruine, 2013), but also across countries with different levels of national health predicting mean levels of masculinity preference for that nation (DeBruine, Jones, Crawford, Welling, & Little, 2010;Penton-Voak, Jacobson, & Trivers, 2004), and in response to pathogen cues (Lee & Zietsch, 2011;.…”
Section: Introductionmentioning
confidence: 99%
“…To illustrate this, the range of mean participant age of studies investigating the link between pathogen avoidance and preference for masculinity is 18.6 to 25.3 years (DeBruine, Jones, Crawford, et al 2010;DeBruine, Jones, Tybur, et al, 2010;Jones et al, 2013;Lee & Zietsch, 2011;Lee et al, 2013;Little et al, 2011;Penton-Voak et al, 2004). Also, when reported, the age of facial stimuli used to assess masculinity preference is of young adults.…”
Section: Introductionmentioning
confidence: 99%
“…However, in times of resource scarcity, men with higher earning potential or relationship commitment were preferred over those genetic qualities (A. J. Lee & Zietsch, 2011). These two lines of research demonstrate the multiple factors that influence mate preferences, which may very well also lead to differences in outgroup prejudice.…”
Section: Future Researchmentioning
confidence: 99%